Perkembangan Pendidikan Indonesia: Evaluasi Potensi Implementasi Merdeka Belajar - Putri, Shena Ananda; Asbari, Masduki; Hapizi, Muhamad Zikri (AGUSPATI RESEARCH INSTITUTA, 2024)
The purpose of this study is to determine whether Indonesia is ready for self-directed learning. This study utilizes a qualitative descriptive method, employing note-taking to gather data by listening to the oral narration from the MetroTV YouTube channel video titled